Konsep Keadilan: Pendekatan Filsafat hukum - Asis, Larasati Fitriani (Taruna Law: Journal of Law and Syariah, 2023)
In interpreting justice, there are various versions of answers and they are often considered unsatisfactory. This gives rise to debate and the meaning of justice becomes a relative formulation. The type of research used in research is library research, which is research related to reading, recording and managing materials used in activities related to research and without using field research. The results of the research show that Plato, Aristotle, and Thomas Aquinas stated that justice is proportional equality, while John Rawls stated that the values ​​of justice included in legal philosophy will be answered by legal philosophy itself. Justice in life is an important need for humans so that everyone can balance demanding their rights and carrying out their obligations in an effort to achieve truth. Thus, truth and obligation must be harmonious and balanced in life.